Pengaruh Pelatihan Simulasi Balut Bidai terhadap Tingkat Kesiapsiagaan Menghadapi Bencana Gempa Bumi di SMA Negeri 1 Kasihan Bantul - Qisthi Sabila; Heri Puspito; Astika Nur Rohmah (Corona: Jurnal Ilmu Kesehatan Umum, Psikolog, Keperawatan dan Kebidanan, 2025)
Indonesia is a country with a high disaster risk, particularly earthquakes. Schools play a strategic role in enhancing students' preparedness for disasters. This study aims to determine the effect of splint bandage simulation training on earthquake preparedness at SMAN 1 Kasihan Bantul. This quantitative study used a pre-experimental one-group pretest-posttest design. The sample consisted of 90 tenth-grade students selected through purposive sampling. The research instrument was a preparedness questionnaire administered before and after the training, analyzed using the Wilcoxon test. The results showed an increase in preparedness from the "less prepared" category to "prepared" and "very prepared" after the training, with a significance value of 0.000. In conclusion, splint bandage simulation training significantly improves students’ earthquake preparedness. Future research is suggested to use animated videos as a more interactive intervention method.